2011
DOI: 10.1176/foc.9.1.foc130
|View full text |Cite
|
Sign up to set email alerts
|

Screening, Brief Intervention, and Referral to Treatment (SBIRT): Toward a Public Health Approach to the Management of Substance Abuse

Abstract: Abstract:Screening, Brief Intervention, and Referral to Treatment (SBIRT) is a comprehensive and integrated approach to the delivery of early intervention and treatment services through universal screening for persons with substance use disorders and those at risk. This paper describes research on the components of SBIRT conducted during the past 25 years, including the development of screening tests, clinical trials of brief interventions and implementation research. Beginning in the 1980s, concerted efforts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
345
0
17

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(369 citation statements)
references
References 129 publications
7
345
0
17
Order By: Relevance
“…5,6 This model of care is widely known as Screening, Brief Intervention, and Referral to Treatment (SBIRT). 7 However, there is little evidence that BAIs improve outcomes or access to specialty care for individuals with moderate to severe alcohol use disorders.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 This model of care is widely known as Screening, Brief Intervention, and Referral to Treatment (SBIRT). 7 However, there is little evidence that BAIs improve outcomes or access to specialty care for individuals with moderate to severe alcohol use disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Most BIs are short sessions lasting only a few minutes and may take place during one or more patient visits. Some models of SBI-called screening, brief intervention, and referral to treatment (SBIRT)-include identifying individuals at risk for alcohol dependence and referring them to formal treatment (Babor et al, 2007). SBIRT models are increasingly being used to address a variety of substance-related issues, including risky drug use and dependence.…”
Section: S Creening and Brief Intervention (Sbi) Formentioning
confidence: 99%
“…Louisiana FIMR began conducting PPOR in each of its nine regions and comparing results with the state overall as part of a Perinatal Needs Assessment Template. The combined findings of FIMR, PPOR, and PRAMS indicated that substance abuse during pregnancy was an important issue to address in reducing excess infant mortality, and the Screening Brief Intervention Referral and Treatment (SBIRT) model [44], an approach to screening and early intervention for substance abuse disorders, was adopted for pregnant and postpartum women.…”
Section: Maturity and Weight At Birth/maturity-and Birth Weight-specimentioning
confidence: 99%